Enhancement of sound absorption of coir fiber using thin layer of kapok fibers. Issue 1 (31st December 2023) - Kassim, Dg Hafizah; Putra, Azma; Ramlan, Roszaidi
ABSTRACT: Natural fiber materials are often favored as a replacement to synthetically made sound absorbers due to its comparable sound absorption properties as well as in the effort to reduce the environmental issue. However, studies are weighted heavily on evaluating the performance of a single or composite fiber and only few studies focused on the multi-layer fiber. In this paper, the sound absorption performance of multi-layer coir and kapok fibers is presented. The kapok fiber is used as the assisting layer element for the coir fiber. A combination of coir fibers with different layer thicknesses and with additional 2 mm thick kapok layer shows significant improvement of the absorption bandwidth. It is also found that the kapok fiber layer placed in between the coir fiber layers show the best improvement of the absorption frequency bandwidth.